Grief, a Wedding Veil, and Bureaucratic Persecution: Becoming Refugee-adjacent in the Aftermath of Tragedy, 1941-1946. Issue 2 (2nd September 2021) - Banko, Lauren
ABSTRACT: The histories of refugees and forced displacement do not often consider the impact of grief and loss upon the family members of such individuals. This essay places the story of one such family member, a young woman who lost her parents, brother, and her fiancé on the sinking of a ship filled with refugees during the Second World War, as the focal point of an exploration of grief, material possessions, and migration, amidst the bureaucratic mechanisms of empire. The story of Doris, a migrant to Mandate Palestine in 1941 and then a repatriate to Great Britain the following year, highlights the ways in which elements of refugeedom intersected with colonialism and empire and restrictions on Jewish migration. I use the fragmentary nature of Doris's archival record to understand her as a 'refugee-adjacent' individual who tried to negotiate hurdles, constraints, and dismissive attitudes of colonial authorities and all the while deal with her own loss and its consequences. Of significance to this historical context is that the grief of refugees and their family members left behind was often unrecognised by colonial and state authorities.